Hidroterritórios da pesca artesanal no Baixo São Francisco: problemáticas (in) sustentáveis sob a ótica das comunidades pescadoras artesanais em Ilha das Flores/SE - Oliveira, Ticiano Rodrigo Almeida (2022)
Territorial conflicts are those that involve social issues, such as a power struggle over the right to use a certain area. In the Lower São Francisco River region, territorial disputes between traditional communities and large enterprises, government works or landowners are common. These disputes result in serious environmental damage and severe changes to the environment, such as the implementation of dams for hydroelectric plants along the course of the river, irrigation and monoculture projects and livestock activities, such as shrimp farming. From the social organization in the face of these conflicts, communities r-exist in their hydroterritories of life and maintain their traditional forms of production. This thesis research was carried out in the fishing quilombo of Bongue, located in Ilha das Flores-SE, and was methodologically based on social cartography, semistructured questionnaires and recorded conversations. The main socio-environmental problems reported by the community were raised in the research, namely: silting of the river; increase in the population of aquatic macrophytes; dumping of effluents in the river bed; irrigation; aquaculture and water salinity. These factors interfere directly in the fishing activity, which is the main source of income for the community. The analysis of the sustainability of fishing activity shows that it fluctuates between low, when it comes to the capture of fish, and increases when it is added to public policies linked to the sector. Social and political factors are fundamental for the continuity of the activity, combined with governance and public investments to maintain water quality and proliferation of fish populations in the region. The relationship between the processes of territorialization, deterritorialization and re-territorialization is of a rhizomatic nature, as it considers the interaction between individuals with the physical environment, with society and with oneself. It is concluded that the affirmation of identity (as traditional quilombola communities and artisanal fisherwomen) is directly related to sociocultural traditions and the work of fisheries. The research thesis question is stated, which says that "Faced with the various scenarios of productive restructuring that have been taking shape for some years in the lower São Francisco, artisanal fishing communities, based on their identity relationships, through the struggle of the remaining quilombolas, seek to overcome the threats to their ways of life, remaining firm in the socio-spatial structure, and acting in the appropriation and management of natural resources, with a view to maintaining the territories, which reaffirms their identity as a social group and traditional community.” This identity is fed back by political articulation, institutional representation, governance capacity and the applicability of public policies. Greater control over public policies related to the fishing sector, the commercialization of sociobiodiversity products and greater applicability of public policies related to the quilombola culture are suggested.